PRESCRIPTIONS OF PRIVATE PRACTITIONERS AND PHYSICIANS OF A TERTIARY CARE HOSPITAL: AN RATIONALITY ASSESSMENT AND COMPARISON. - R. SUDAR CODI; SAMIYA KHAN; K. MANIMEKALAI.; G.SOMASUNDARAM. (International Journal of Pharma and Bio Sciences, 2015)
Compare the rationality of prescriptions between private practitioners and physicians of a tertiary care hospital. A prospective study was done by reviewing 150 prescriptions each of private practitioners and physicians of a tertiary care hospital over a period of 2 months. The rationality assessment was done using the method adopted by Gajjar. Collected data entered and analyzed using Microsoft office Excel 2010 computer software. Statistical tests were applied and p<0.05 was considered as statistically significant.120 prescriptions were rationally prescribed by physicians of a tertiary care hospital. 28 were semi rational and only 2 prescriptions were irrational. 46 prescriptions of the private practitioners were rational, 88 semi rational and 16 were irrational (P<0.001). Private practitioners prescribe more irrational prescriptions. Our studies on the prescribing pattern of various sectors needed to make the doctors aware of the irrational drug use. Also, the art of prescription writing and the need for rational prescribing should be stressed during the medical school.